2006
DOI: 10.1007/s00464-005-0405-1
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic cholecystectomy under spinal anesthesia

Abstract: Laparoscopic cholecystectomy with low-pressure CO2 pneumoperitoneum can be successfully and safely performed under spinal anesthesia. Furthermore, it seems that spinal anesthesia is associated with minimal postoperative pain and at least an equally good recovery as with general anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
1
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 8 publications
3
81
1
4
Order By: Relevance
“…This confirms that the anesthesiologist by inflating the stomach while ventilating with a face mask during induction and before intubation is mainly responsible for the need of a NG tube. Unlike other studies [9] this was a comparative study and the majority of patients had a better experience with postoperative analgesia than those undergoing general anesthesia during this period. This is particularly true during the first 6 h after the procedure, most likely due to two factors: the absence of a tracheal tube and its discomforts and the presence of an adequate level of analgesia and analgesia in the first postoperative hours due to the choice of agents used in the subarachnoid space.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This confirms that the anesthesiologist by inflating the stomach while ventilating with a face mask during induction and before intubation is mainly responsible for the need of a NG tube. Unlike other studies [9] this was a comparative study and the majority of patients had a better experience with postoperative analgesia than those undergoing general anesthesia during this period. This is particularly true during the first 6 h after the procedure, most likely due to two factors: the absence of a tracheal tube and its discomforts and the presence of an adequate level of analgesia and analgesia in the first postoperative hours due to the choice of agents used in the subarachnoid space.…”
Section: Discussionmentioning
confidence: 98%
“…Unlike other authors [9] a NG tube was not used routinely in both groups. The determination of its real need was part of the protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such replacement is not for avoidance of general anesthesia (G.A. ), but for providing the benefits of regional anesthesia 3 to manage the patient with significant medical problems. Usually, classical intrathecal approach at lumbar region is not sufficient enough to satisfy the expectation of surgeon regarding muscular relaxation of anterior abdominal wall to achieve a relaxed and undisturbed surgical field and even at the time of laparoscopic procedure it is highly objectionable.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Several studies have demonstrated that LC with the patient under spinal anaesthesia was feasible and Section: Anaesthesia safe and was associated with better postoperative pain control. [12][13][14][15][16][17] The choice of anaesthesia for laparoscopic surgery has for long been general anaesthesia because of the following reasons: a) The patient's airway is under the control of the anaesthesiologist, b) Minimal chances of aspiration due to gastric regurgitation, c) No patient discomfort and shoulder pain due to pneumoperitoneum, d) Controlled ventilation to manage hypercarbia, e) No patient discomfort due to change in position, f) No complications due to decreased sympathetic outflow such as hypotension and bradycardias seen with regional anaesthesia, g) Better hemodynamic status. [9,11] The aim of this prospective randomized study was to compare the surgical outcome of LC performed with the patient under spinal anaesthesia with that of LC performed with the patient under general anaesthesia in the management of symptomatic uncomplicated gallstone disease.…”
Section: Introductionmentioning
confidence: 99%